Influence of Financial Literacy, Financial Technology, Hedonism Lifestyle, and Self-Control on Financial Management Behavior of Undergraduate Students at the University of Bengkulu - Refianti, Refianti; Zoraya, Intan (Universitas Bengkulu, 2024)
The research aims to find out whether financial literacy, financial technology, hedonism lifestyle, self-control influence the financial management behavior of Bengkulu University students. The research method used in this study is quantitative using primary data collected through questionnaires distributed online through various social media. This study distributed questionnaires to 120 respondents from students of the University of Bengkulu who has a bussiness and then processed statistically using IBM SPSS 24 and multiple linear regression methods. The research finding that financial literacy has a positive and significant effect on financial management behavior, financial technology has no effect on financial management behavior, hedonism lifestyle has no effect on financial management behavior, and self-control has a positive and significant effect on financial management behavior.